Shelley's Living Artistry. - Callaghan, Madeleine (Liverpool English Texts and Studies LUP., 2017)
This study of the poetry and drama of Percy Bysshe Shelley reads the letters and their biographical contexts to shed light on the poetry, tracing the ambiguous and shifting relationship between the poet's art and life.